Update on Huntington's disease: Advances in care and emerging therapeutic options. Issue 3 (March 2015) - Zielonka, Daniel; Mielcarek, Michal; Landwehrmeyer, G. Bernhard
Abstract: Introduction: Huntington's disease (HD) is the most common hereditary neurodegenerative disorder. Despite the fact that both the gene and the mutation causing this monogenetic disorder were identified more than 20 years ago, disease-modifying therapies for HD have not yet been established. Review: While intense preclinical research and large cohort studies in HD have laid foundations for tangible improvements in understanding HD and caring for HD patients, identifying targets for therapeutic interventions and developing novel therapeutic modalities (new chemical entities and advanced therapies using DNA and RNA molecules as therapeutic agents) continues to be an ongoing process. The authors review recent achievements in HD research and focus on approaches towards disease-modifying therapies, ranging from huntingtin-lowering strategies to improving huntingtin clearance that may be promoted by posttranslational HTT modifications. Conclusion: The nature and number of upcoming clinical studies/trials in HD is a reason for hope for HD patients and their families. Highlights: Gene silencing therapy is very close and most expected therapeutic option for HD. Currently symptomatic therapy in HD improve motor and behavioral spheres. Standards on care in HD refer to most patients' problems improving their QoL.